The Influence of Role Playing Method on Speaking Skills of Grade 4 Students at Muhammadiyah 4 Elementary School Malang City - Fardana, Yudistira; Khasanah, Niswatun; Iswatiningsih , Daroe; Ambawono, Gancar Pramistri; Rahayuningsih , Setiti (Universitas Nusantara PGRI Kediri, 2025)
Speaking skills are an important aspect in education, but are often overlooked in conventional teaching methods. Role playing offers an innovative approach by creating real situations where students can practice speaking actively and interactively. This study is a classroom action research. This study aims to determine the improvement of speaking skills of grade IV students of SD Muhammadiyah 4 Malang City. The research was conducted on 24 students consisting of 18 male students and 6 female students and 1 grade IV education teacher of SD Muhammadiyah 4 Malang City. Data collection used observation and test techniques. Data analysis used qualitative and quantitative descriptive. The results of the study showed that the application of the role playing method was able to improve students' speaking skills in learning Indonesian in grade IV of SD Muhammadiyah 4 Malang City. This is proven by the increase in the average value of students' speaking skills between cycle I and cycle II, namely from cycle I, students' speaking skills reached 54.73% with 10 students completing, and 14 students entered the category of